2011
DOI: 10.1089/ten.tec.2011.0098
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Noninvasive Monitoring of Dissolved Oxygen Concentration Within an Implanted Tissue-Engineered Pancreatic Construct

Abstract: The function of an implanted tissue-engineered pancreatic construct is influenced by many in vivo factors; however, assessing its function is based primarily on end physiologic effects. As oxygen significantly affects cell function, we established a dual perfluorocarbon method that utilizes 19 F nuclear magnetic resonance spectroscopy, with perfluorocarbons as oxygen concentration markers, to noninvasively monitor dissolved oxygen concentration (DO) in bTC-tet cell-containing alginate beads and at the implanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 35 publications
1
37
1
Order By: Relevance
“…Eleven publications reporting information on PFCE R 1 oxygen sensitivity were identified. 28,[30][31][32][33][34][35][36][38][39][40] One was excluded for inconsistent reporting of data 38 and another was excluded for results that differed from other reported data by several standard deviations, 40 leaving eleven reported calibrations 28,[30][31][32][33][34][35][36]39 that were combined with our data for analysis. Oxygen sensitivity decreased (-6.39 · 10 -5 mmHg -1…”
Section: Comparative Data Collection and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven publications reporting information on PFCE R 1 oxygen sensitivity were identified. 28,[30][31][32][33][34][35][36][38][39][40] One was excluded for inconsistent reporting of data 38 and another was excluded for results that differed from other reported data by several standard deviations, 40 leaving eleven reported calibrations 28,[30][31][32][33][34][35][36]39 that were combined with our data for analysis. Oxygen sensitivity decreased (-6.39 · 10 -5 mmHg -1…”
Section: Comparative Data Collection and Analysismentioning
confidence: 99%
“…PFC-loaded alginate beads implanted into the rodent kidney capsule, peritoneal cavity, and quadriceps femoris muscle reveal a hypoxic environment unconducive to islet survival. 38,[42][43][44] Macroencapsulated cell systems, however, are often implanted into the subcutaneous space 2 and these studies, limited to microencapsulation, did not examine the oxygen availability of this site.…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of transplant volumes to normalize glycemia were based on reported insulin secretion from microencapsulated βTC-tet cells that restored normoglycemia in STZ-induced diabetic mice (13). EINS data from Figure 1C indicated that 7.5 mL microcapsules would be sufficient to control glycemia, but due to space restrictions, 3 mL (corresponding to 9x10 7 EINS cells) was the maximum volume attempted for transplant in mice.…”
Section: Resultsmentioning
confidence: 99%
“…Within the context of the model of ovarian cancer used in our studies, it has been previously noted that the intraperitoneal cavity in mice is hypoxic [38]. As such, progression of disease in this environment may be strongly influenced by the expression or inhibition of HIF-1 alpha and/or HIF-2α.…”
Section: Discussionmentioning
confidence: 99%